(untitled) (Research, Society and Development, 2024)
Introduction: Nursing needs to support the ethical training of its professionals in the construction of scientific, technical, ethical and legal knowledge to ensure care that is free from harm resulting from malpractice, negligence or recklessness, as stated in Article 45 of Resolution 564/2017 of the Federal Nursing Council (COFEN). Objective: This study aims to evaluate ethical incidents in nursing and their causes, as this reflection is essential for these professionals in the context to which they are inserted. Methodology: An integrated literature review was carried out, with the aim of collecting and summarizing the scientific knowledge already developed on this subject in order to better understand it. Analysis and discussion of results: Firstly, analyzing and discussing the topic was an arduous process due to the difficulty of finding studies that touched on it. Despite this, it was observed that Ethical Occurrences in Nursing occur due to the overload of its professionals due to the number of patients and because they have several jobs as a result of low pay. Furthermore, some studies have reported that a contributing factor to these incidents is the lack of information about the profession’s ethical issues during the undergraduate process, making future professionals uninformed about their limitations, obligations and rights. Conclusion: Therefore, it was found that it is necessary to encourage research into Ethical Occurrences in Nursing in order to understand this phenomenon and seek to elucidate and remedy it in the best way. In addition, educational institutions should emphasize the ethical issues of the profession so that future professionals can protect themselves and comply with Article 45 of COFEN Resolution 564/2017.